FROM CURATORING TO TUTOR: FEATURES OF STUDENTS’ IMAGINATION - Яновська, Світлана Германівна; Туренко, Римма Леонардівна; Базилевська, Людмила Олександрівна (Visnyk of V.N. Karazin Kharkiv National University. Series Psychology, 2020)
The article deals with the peculiarities of students’ ideas about curating and tutoring in higher education institutions. Used: the methodology of diagnostics of interpersonal relations (T. Leary) to determine the peculiarities of students’ ideas about the personality of the curator and tutor and the specific interaction of students with the curators and tutors; questionnaire method to determine the features of the curator and tutor; C. Osgud’s semantic differential method for determining the self-esteem characteristics of curators and tutors. It has been shown that students’ perceptions of curating and tutoring have a lot in common: almost half of the respondents do not see a difference between the concepts under study. Students identify them as mentors, leaders who can lead, impart and teach. But leadership is more often associated with curating than with tutoring. The tutor, in turn, is more of a friend, mentor, and tutor. It has been identified that students describe curating in relation to the main tasks of working in an academic group, namely, calling them organizers and people who can help and are responsible. Tutors are also described more as a friend, assistant, mentor and tutor, that is, a teacher who is more likely to help and teach, develop skills. Problems of students’ attitude towards curators were identified. Almost a third of respondents believe that a supervisor does not perform their duties and communicating with him causes anxiety, anxiety in students. This may be due to the supervisor’s attribution of the control and enforcement functions that apply to students’ poor performance of their duties. Statistically significant differences have been identified: tutoring has significantly higher performance than octant curating: “Authorities,” “Friendliness,” “Altruism.” Thus, the tutor can be described as a more confident person, a persistent, responsible, responsible student, caring, selfless and responsive, prone to cooperation, compromise in solving problems and conflicts, sociable, friendly in relationships. It has been concluded that the tutoring institute has considerable potential in enriching and expanding the traditional teacher-student relationship, contributing to the personal growth of students, and expanding educational resources.